2020
DOI: 10.18472/sustdeb.v11n1.2020.28152
|View full text |Cite
|
Sign up to set email alerts
|

Reforest or perish: ecosystem services provided by riparian vegetation to improve water quality in an urban reservoir (São Paulo, Brazil)

Abstract: We estimated the economic value of ecosystem services provided by the legally protected vegetation in riparian zones (RPA- riparian protected areas) of watercourses of the Guarapiranga Reservoir watershed (São Paulo, Brazil), considering two scenarios: (i) the value of ecosystem services provided if the RPA recovery complies with the applicable environmental legislation; and (ii) the year 2030, maintaining the urbanization rate and the loss of vegetation cover in the watershed observed between 1986 and 2010. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The results obtained in that study demonstrated the potential of creating riparian UGSs to rehabilitate polluted rivers. A study conducted on ecosystem services in a riparian protected area (RPA) in São Paulo estimated that 5917.5 ha of the reforested RPA could reduce the cost of water treatment by USD 181,774 per 1000 m 3 [46]. Additionally, Figure 5 shows a cluster of districts with higher population densities and larger impervious areas (roads and concrete pavements) and built spaces.…”
Section: Interaction Of Urban Green Spaces and Intra-urban Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained in that study demonstrated the potential of creating riparian UGSs to rehabilitate polluted rivers. A study conducted on ecosystem services in a riparian protected area (RPA) in São Paulo estimated that 5917.5 ha of the reforested RPA could reduce the cost of water treatment by USD 181,774 per 1000 m 3 [46]. Additionally, Figure 5 shows a cluster of districts with higher population densities and larger impervious areas (roads and concrete pavements) and built spaces.…”
Section: Interaction Of Urban Green Spaces and Intra-urban Elementsmentioning
confidence: 99%
“…The results obtained in that study demonstrated the potential of creating riparian UGSs to rehabilitate polluted rivers. A study conducted on ecosystem services in a riparian protected area (RPA) in São Paulo estimated that 5917.5 ha of the reforested RPA could reduce the cost of water treatment by USD 181,774 per 1000 m 3 [46].…”
Section: Interaction Of Urban Green Spaces and Intra-urban Elementsmentioning
confidence: 99%